2018
DOI: 10.1080/09853111.2018.1494776
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic evidence for active tectonic deformation in the coastal part of Eastern Black Sea, Eastern Pontides, Turkey

Abstract: The Eastern Pontides (EP), which is the under transpressional deformation zone, is an active mountain belt that has been rising rapidly since the Cenozoic era because of the Arabian-Eurasian convergence. Morphometric studies have been performed to investigate the tectonic activity of this region and better understand the characteristics of the faults geomorphologically; the faults control the mountain fronts in the drainage basin of the EP. The results show the Hypsometric Curve (HC)-Hypsometric Integral (0.37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 66 publications
1
16
0
2
Order By: Relevance
“…High SL values further suggest that development of the sub-basins was controlled by recent tectonic activity in the study area. A similar result was also found in Softa et al (2018)'s study. Their results indicated that each river has a knickpoint which marked fault zones determined in the area.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…High SL values further suggest that development of the sub-basins was controlled by recent tectonic activity in the study area. A similar result was also found in Softa et al (2018)'s study. Their results indicated that each river has a knickpoint which marked fault zones determined in the area.…”
Section: Discussionsupporting
confidence: 90%
“…This shows that the zone is tectonically active in the Eastern Pontides. At the same time, high SL values and those having knickpoints show that the drainage basins analyzed are in disequilibrium and the ephemeral feature of the area is due to incomplete uplifting (Softa et al, 2018). In the southern sector, the SL values of the Korucak stream are greater than the other streams.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…New faults were also identified based on field observations, Hack profile, and SL-indices in Chitwan dun, central Nepal. OSL dating derived ages of the landforms support distinct climate-tectonic coupling events responsible for landscape evolution in Chitwan dun García-Delgado and Velandia (2020) Structural and geomorphic indices-based study indicates greater tectonic activity and uplift rates for the northern San Lucas Range, in the Northern Andes Transform setting Arrowsmith and Zielke (2009) Field evidences, paleoseismic analysis, and high-resolution LiDAR DEM were used to trace the active Cholame segment of San Andreas Fault (SAF) to understand tectonic geomorphology of SAF Softa et al (2018) Transpressional deformation zone, the Eastern Pontides (EP), is the active deformation zone and has a "push-up" geometry in conjunction with the North Anatolian Fault high. The EP exhibits high tectonic activity based on geomorphic indices and more than 0.5 mm/yr upliftment along the thrust faults of the Black Sea Fault (BSF) and Borjomi-Kazbegi Fault (BKF) in the active mountain belt…”
Section: Bibliographymentioning
confidence: 99%